Effects of physiotherapy on degenerative cerebellar ataxia: a systematic review and meta-analysis - Matsugi, Akiyoshi; Bando, Kyota; Kondo, Yuki; Kikuchi, Yutaka; Miyata, Kazuhiro; Hiramatsu, Yuichi; Yamanaka, Yuya; Tanaka, Hiroaki; Okuda, Yuta; Haruyama, Koshiro; Yamasaki, Yuichiro (Frontiers in Neurology, 2025)
BackgroundEvidence of the effectiveness of physiotherapy, including muscle strength training, coordination training, aerobic exercise, cycling regimen, balance training, gait training, and activity of daily living training, in patients with degenerative cerebellar ataxia (DCA) was insufficient for clinical decision making. We aimed to explore clinical outcomes and examine the parameters associated with physical impairment and activity in people with DCA based on preregistration (PROSPERO: CRD42024493883).MethodsThe PubMed, Cochrane Library, CHINAL, and PEDro databases were searched for relevant randomized controlled trials (RCTs). Data extraction, quality assessment, and heterogeneity analyses were conducted. The Grading of Recommendations Assessment, Development, and Evaluation framework (GRADE) was used to assess the quality of evidence, and a meta-analysis was performed.ResultsEighteen RCTs, which included 398 participants, showed a serious risk of bias (RoB) and low certainty of evidence for this primary outcome. For meta-analysis, 315 patients assessed based on the Scale for Assessment and Rating of Ataxia (SARA) were included. Overall, physiotherapy significantly reduced SARA scores (MD = −1.41, [95% CI: −2.16, −0.66]); the subgroup analysis showed that the following interventions exerted significant effects: multi-aspect training program (5 studies, MD = −1.59, [95% CI: −5.15, −0.03]), balance training (3 studies, MD = −1.58, [95% CI: −2.55, −0.62]), and aerobic training (3 studies, MD = −1.65, [95% CI: −2.53, −0.77]). By contrast, vibration (2 studies, MD = −0.56, [95% CI: −2.05, 0.93]) and dual-task training (1 study, MD = 0.24, [95% CI: −6.4, 6.88]) exhibited no significant effects.ConclusionPhysical therapy, especially multi-aspect physical therapy such as muscle strengthening, coordination training, gait training, and ADL training, may reduce DCA symptoms. Further, balance and aerobic training can be added to the program. However, the estimated effect size may change in future studies because of the serious RoB, very low certainty of evidence, and high heterogeneity with SARA as the primary outcome. High-quality RCTs are required to establish evidence for the effectiveness of physical therapy in patients with DCA.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=493883, identifier: CRD42024493883.